ANALYSIS OF COMPETITIVENESS SMI BATIK IN BOGOR CITY - Defytri Nur Agustine; Nikensari, Sri Indah; Sariwulan, Rd. Tuty (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
This study aims to identify and analyze the competitiveness of batik SMEs in Bogor City. Data were obtained from interviews with 3 batik SMEs in Bogor City using descriptive qualitative methods using SWOT analysis. The results of this study indicate that if you carry out a strategy carried out by each SMI using the SO strategy, that is a strategy that uses strength to take advantage of the opportunities that exist in each IKM in the city of Bogor.